Prior exposure to non‐pathogenic calicivirus RCV‐A1 reduces both infection rate and mortality from rabbit haemorrhagic disease in a population of wild rabbits in Australia. Issue 2 (17th December 2017) - Cooke, B. D.; Duncan, R. P.; McDonald, I.; Liu, J.; Capucci, L.; Mutze, G. J.; Strive, T.
Summary: Mortality caused by rabbit haemorrhagic disease virus (RHDV) in wild rabbits is reduced in parts of Australia where the related, non‐pathogenic calicivirus RCV‐A1 is endemic. Laboratory experiments previously showed that prior infection with RCV‐A1 enabled rabbits to better withstand subsequent infection with highly virulent RHDV, and this was assumed to explain higher survival. Here, we analyse serological data from the field suggesting that reduced mortality rates among wild rabbits may also result from rabbits previously infected with RCV‐A1 having a reduced likelihood of RHDV infection. We discuss the possible mechanisms underlying this finding and its implications. The methods we describe for analysing field data gave far greater insights into epidemiological processes and virus interactions than gained from reporting basic seroprevalence rates alone.